2012
DOI: 10.1016/j.ssc.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram and oxygen annealing effect of FeTe1−Se iron-based superconductor

Abstract: Phase diagrams of as-grown and O 2 -annealed FeTe 1-x Se x determined from magnetic susceptibility measurement were obtained. For as-grown samples, the antiferromagnetic order was fully suppressed in the range region x ≥ 0.15, and weak superconductivity appeared when x ≥ 0.1.Beginning at x = 0.5, weak superconductivity was found to evolve into bulk superconductivity.Interestingly, for O 2 -annealed samples, complete suppression of magnetic order and the occurrence of bulk superconductivity were observed when x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 27 publications
3
69
1
Order By: Relevance
“…However, in iron-chalcogenide FeTe 0.6 Se 0.4 , the long-range SDW is already totally suppressed according to the phase diagram, 56,57 which indicates the origin of the Dirac cone state in iron-chalcogenides may be different from that in iron pnictides. Here, we should point out that although the long-range SDW is proven to be suppressed by Se doping, the SDW fluctuation may still survive.…”
Section: 50mentioning
confidence: 96%
“…However, in iron-chalcogenide FeTe 0.6 Se 0.4 , the long-range SDW is already totally suppressed according to the phase diagram, 56,57 which indicates the origin of the Dirac cone state in iron-chalcogenides may be different from that in iron pnictides. Here, we should point out that although the long-range SDW is proven to be suppressed by Se doping, the SDW fluctuation may still survive.…”
Section: 50mentioning
confidence: 96%
“…Only the oxygen-annealed sample shows a distinct superconducting behavior. Kawasaki et al [70] reported that annealing in oxygen is effective for not only FeTe 1-x S x but also FeTe 1-x Se x . Figure 13 shows the temperature dependence of magnetic susceptibility for Next, we discuss the relation between bulk superconductivity and antiferromagnetic fluctuations.…”
Section: Annealing Effects Of Fete-based Superconductorsmentioning
confidence: 99%
“…Within a picture of spin-fluctuation mediated superconductivity a susceptibility peaked at the connection vector [47,50], while the right side shows the behavior of Fe 1+δ Te x Se 1−x as a function of x following [47,103,104] Superconductivity can also be produced by alloying with FeS [105,106].…”
Section: Features Of Fe-pnictide Superconductorsmentioning
confidence: 99%